PENGGUNAAN METODE RCFA UNTUK MEMPERBAIKI KERUSAKAN SISTEM KELISTRIKAN MOTOR UTAMA MESIN FRAIS ACIERA F3 - Mustaqim, Mustaqim; Septiarditian, Septiarditian; Feriadi, Indra; Rivai, Muhammad; Aswin, Fajar (Politeknik Manufaktur Negeri Bangka Belitung, 2025)
Damage to the electrical system of the Aciera F3 milling machine caused the main motor to fail to operate, disrupting practical activities at the Bangka Belitung State Manufacturing Polytechnic. This study aims to identify the root cause of the failure and carry out repairs using the Root Cause Failure Analysis (RCFA) approach with the 5 Why technique. The research stages include data collection through technician interviews, visual inspections, and functional testing of the electrical system. The analysis revealed that the damage resulted from a short circuit in the C2 contactor, caused by component aging and the absence of routine inspections. Corrective action was taken by replacing the damaged contactor and auxiliary contact components. As a preventive measure, an electrical inspection checklist was developed to support scheduled maintenance. Post-repair testing showed that the electrical system functioned normally and the machine could operate according to standard specifications. The application of the RCFA method proved effective in resolving the problem comprehensively and laying the foundation for a reliability-based maintenance system.